تقييم معلومات الممرضات حول إجراءات ضبط العدوى في قسم الحواضن - أحمد, آنا (Latakia University Journal -Medical Sciences Series, 2019)
يعد التركيز على ضبط العدوى في قسم الحواضن أمراً هاماً كونه يستقبل حالات مرضية حرجة تحتاج إلى مراقبة وعناية تمريضية مركزة، إذ يتوجب على الكادر التمريضي امتلاك معلومات كافيه عن إجراءات ضبط العدوى في قسم الحواضن من لحظة دخول حديث الولادة إليه وحتى تخريجه منها, لذلك جاءت الدراسة الوصفية الحالية لتقييم معلومات 50 ممرضه حول إجراءات ضبط العدوى في قسم الحواضن في كل من مشفى تشرين الجامعي ومشفى التوليد والأطفال الوطني في اللاذقية, وقد تم اختيارهن بطريقة العينة المتاحة, واستخدم استبيان لجمع البيانات صممته الباحثة لهذا الغرض, وأظهرت النتائج أن لدى أقل من ثلاثة أرباع الممرضات مستوى معلومات متوسط حول إجراءات ضبط العدوى, وأقل من خمسهن لديهن مستوى معلومات جيد. وأوصت الدراسة بضرورة التقييم المستمر لمعلومات الممرضات, وإجراء دورات تثقيفية بشكل دوري لهن حول إجراءات ضبط العدوى في قسم الحواضن, ودراسة العوامل المؤثرة على مستوى معلومات الممرضات في قسم الحواضن حول إجراءات ضبط العدوى. The focus on infection control in the incubator ward is important as it receives critical conditions requiring monitoring and intensive nursing care. The nursing staff should have adequate information about infection control standards in the incubator ward from the moment of entry into the newborn until it is discharged. Therefore, the current descriptive study aims to Assessment knowledge of 50 nursing about Infection control procedures at incubator ward in both Tishreen university Hospital and Obstetric and Children Hospital in Lattakia. They were selected in the available sample method and used a questionnaire to collect data designed by the researcher for this purpose. The results showed that less than three-quarters of nurses had an average level of information about infection control procedures, and less than a fifth had a good level of information. The study recommended the continuous assessment of nurses' information, periodic training sessions on infection control procedures in the incubation ward, and the factors influencing the level of nurse information in the incubation ward on infection control procedures.